Trabalho de graduação interdisciplinar (TGI): origens e problematização da proposta implantada em 1971 na Faculdade de Arquitetura e Urbanismo da Universidade de São Paulo (FAU/USP). - Malacrida, Sérgio Augusto (2004)
The subject of this research is the Interdisciplinary Graduation Work the Brazilian Final Works Modality of the Architecture Course implanted in 1971 by Faculdade de Arquitetura e Urbanismo da Universidade de São Paulo (School of Architecture and Urbanism of São Paulo University) (FAU/USP) it s remote origin and the formulation of the proposed model by architect and teacher Hélio de Queiroz Duarte, at that period teacher and coordinator of the 5th year course. He objectified the study of TGI because of it s presumed importance in teaching architecture and urbanism in Brazil, the influence of it s conception base of the Final Graduation Work (TFG), actual instrument adopted by the country s courses in this area, through Portaria/Mec 1779/94. In the XIVth century, yet in the medieval corporations, it was possible to identify a work of the final qualification moment of the training course ministered in the workshops; the Masterpiece of the future mechanical art s master, more precisely that of construction. However, the First academic final work of Architecture s Course developed in a formalized teaching was identified in the XVIIIth Century in the Royal Academy of Architecture (Academia Real de Arquitetura) later incorporated to the Fine Art s School (Escola de Belas Artes) of Paris: Rome s Grand Award. The model, consecratory of the Greek/Roman style and of classic ideals, inspired the Travel Awards to Italy, which crown the best works of the Fine Art s School of Rio de Janeiro, founded in 1816, with the arrival of the Royal Family and of the French Mission, part of which was the higher course of Brazilian architects formation beginning from 1826. Another Final Work identified was the Diplomation Test from the Special Architect School in Paris, founded in 1865 influenced by the School of Engineering (Escola Politecnica) which model of teaching opposed that of Fine Arts, proving to be more modern in the use of new technologies and available materials. This model influenced also the modernization of architecture and Urbanism teaching, in Brazil. In 1847, was created the Engineering School of Rio de Janeiro and in 1894 that of São Paulo, with the graduation course of engineer/architect. This course culminates with the creation, in 1948, of the Faculdade de Arquitetura e Urbanismo da Universidade de São Paulo (School of Architecture and Urbanism of São Paulo University) (FAU/USP) separating the architecture and urbanism courses from that of engineering. The Engineering School, however, presented 5th year works with a classical tendency. In FAU, the pursuit for autonomy echoed in FAU, reflected in the Debate Forum of the 60 decade and the implantation of TGI in the 70 decade. The investigated Course s Final Works of Architecture turned out to be academical, social/historical instruments, representing teaching models, the schools that instituted them and the implantation context. They work as a passport for professionalization, actually conferred by the diploma. The study of the TGI model proposed by Helio de Queiroz Duarte and by the implantation model adapted by FAU/USP brought a light to the principles of the institution of the Final Works of the Brazilian Course of Architecture and Urbanism in its search for a modern teaching, basically turned to academical, technological sociological and construction questions which indicate the professionalization. In this sense, it serves as an element of study for the future reorganization of TFG.